A aprendizagem histórica em oxímoro : o jogo eletrônico e o câmbio entre a cultura de presença e a cultura de sentido - Freitas, Rafael Reinaldo (2023)
This research aims to understand historical learning by investigating the involvement of young high school students with aestheticized historical narrative in electronic games. Situated within the research paradigm of Historical Education and the foundations of Situated Historical Cognition (SCHMIDT, 2009), this study sought to elucidate the phenomenon of learning history as possessing two distinct yet non-contradictory logics: dynamics of pre-cognitive order, perceived in the emotional engagement with the historical narrative presented there, and cognitive order, interpretation of the lived experience and manifested meaning in the historical narrative of young students. To this end, it endeavors to establish a dialogic debate between the theory of Historical Consciousness proposed by Jörn Rüsen (2015) and Martin Heidegger's ontological philosophy, aiming to delineate the concern with feeling and emotion, as seen in mood as an opening to the world (HEIDEGGER, 2007), as constitutive of the aesthetic dimension of historical culture that catalyzes the productive action of historically narrating, among young students in educational contexts. This investigative profile arises within the classroom experience and from the previous investigative endeavor (FREITAS, 2017), which revealed the need to explore other factors of learning history beyond hermeneutics, while not detaching from the cognitive dimension, but rather explicitly elucidating the production of presence (GUMBRECHT, 2004). In order to elucidate this movement, it is explained that the debate around these two dimensions extends to the realm of historical research and its impasse between truth and fiction, a question that overflows into the teaching of history. With Heidegger (2016), the triumph of the idea of truth as the result of the method is questioned, and aesthetics is opened up as a producer of truths. From this, the explanation of intersubjective action (FRONZA, 2012) and the aesthetics of electronic games (BOGOST, 2011) allowed us to inventory openings to the human past, seen as an intramundane being, through humor (HEIDEGGER, 2011), promoting engagement with the typical agency of electronic games, a revealing phenomenon of the worldview of young students in their historical consciousness.